THE INFLUENCE OF ENTREPRENEURIAL CULTURE ON ENTREPRENEURIAL INTENTION AMONG BUSINESS STUDENTS - Genoveva Genoveva (FIRM Journal of Management Studies, 2019)
The number of entrepreneurs in Indonesia increased in 2017 from 1.67% to 3.10% from 225 million Indonesians. But the number is still less than the number of our neighboring entrepreneurs, Malaysia has 6% entrepreneurs, Singapore 7% and Thailand 5%. Increasing the number of entrepreneurs shows the increasing economic growth of a country, therefore the government made various efforts encourages the growth of the number of entrepreneurs in Indonesia, through education in this case the ministry of education provides an appeal for entrepreneurship to be included as part of the curriculum, both at the high school and university level. Entrepreneurship education giving the students experiances of various technical and skills to become more confident as an entrepreneurs. Beside of education, motivation, personality and family background also determine entrepreneurial intention. The aims of this research is to find out the entrepreneurial education, entrepreneurial motivation, entrepreneurial personality and family background influence on entrepreneurial intention. This study uses a sample of 326 business students of President University. The data collection using google docs that is spreaded via whatshapp, line and email. The result of the study were processed using SPSS version 22. The conclusion show that independent variables (entrepreneurial education, entrepreneurial motivation, entrepreneurial personality and family background) influence on entrepreneurial intention with affected 54.4% and the rest by the others factors.